Domestic Dogs Exposed to Orthopoxvirus in Urban Areas of Brazil - Débora de Meneses; Ana G. Stoffella-Dutra; Vicenzo S. Blaso; Iara M. de Almeida; Karolina L. Dias; Iago José da S. Domingos; Gabriela P. Ribeiro; Wendel Coura-Vital; Alexandre B. Reis; Thallyta M. Vieira; Giliane de S. Trindade (Viruses)
Domestic animals can share viral pathogens with humans, acting mainly as a bridge host. The Orthopoxvirus genus hosts important zoonotic species that have emerged in urban areas worldwide. Nevertheless, the role of companion animals, such as dogs and cats, in the circulation of orthopoxviruses in urban areas remains poorly understood. Therefore, the objective of this study was to evaluate the presence of neutralizing anti-orthopoxvirus antibodies in serum samples from owned dogs from three municipalities in Minas Gerais, as well as the presence of the C11R and A56R orthopoxviruses genes. The presence of neutralizing antibodies was detected in 14.3% of the animals investigated. However, no sample was positive for the presence of the genes investigated. Further study of the population of dogs in urban areas may prove a valuable tool for understanding the spread of orthopoxviruses in urbanized areas of Brazil.